Rumah Haji Ahmad, Parit Sangit, Batu 10 Semerah, Batu Pahat, Johor - Hussein Salleh; Hashim Mohd. Salleh; Hamshani Surat; Kamariah Ithnin; Rozita Ariani Yusoff; Rosni Harun (KL : UTM, 1981)
Tesis (Diploma Senibina) - Universiti Teknologi Malaysia, 1981